Palladium- and nickel-catalyzed synthesis of thioethers via thioesters – Aryl halides coupling. (12th April 2023) - Cao, Han; Shi, Yijun; Ma, Jie; Yan, Peng; Cong, Xingshun; Bie, Fusheng
Graphical abstract: Highlights: A development protocol for synthesis of thioethers using cyclohexyl thioesters as sulfur-containing functional groups. Both Pd- and Ni-based catalysts are developed and it has complementary effect in yields and reaction rates. Thianthrene, precursor to thianthrene S-oxide (TTO), has been synthesized under these protocols. Abstract: This paper describes the development of a cross-coupling reaction of aryl halides with cyclohexyl thioesters. Both Pd- and Ni-based catalysts are developed and it has complementary effect in yields and reaction rates. The synthetic strategies displayed a wide functional group tolerance and expanded the portfolio of cross-coupling for the synthesis of valuable thioethers.